Schreiben auf statuarischen Monumenten: Aspekte materialer Textkultur in archaischer und frühklassischer Zeit - Dietrich, Nikolaus; Fouquet, Johannes; Reinhardt, Corinna (Materiale Textkulturen, 2020)
Considering Greek statue inscriptions from the archaic and early classical periods, this book emphasizes inscription practices without losing sight of issues of semantics. The analysis focuses on the layout and graphical or ornamental features of the inscriptions. With this approach, for the first time questions of aesthetics and materiality, which were previously examined only for the statues themselves, are also brought to their inscriptions
Keywords: Antike; Epigraphik; Plastik